Keragaman Burung di Ekosistem Mangrove Kecamatan Sungai Apit Sebagai Bahan Pengayaan Mata Kuliah Keanakeragaman Hayati Makhluk Hidup - hadi, hadi purwanto (Unit Pelaksana Praktik Kependidikan Terpadu Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Riau, 2024)
The purpose of this study was to identify bird species, evaluate bird interactions with the environment, understand their impact on the sustainability of mangrove ecosystems, as well as to produce local potential-based handout development to overcome students' difficulties in understanding the concept of bird population and diversity in the mangrove ecosystem environment, which is caused by a teaching approach that is too theoretical. The research was conducted in the Mangrove Ecosystem of Sungai Apit District, Siak Regency, Riau. The research method involved a combination of descriptive and developmental research, using a sampling technique using IPA Count. The results identified 24 bird species with a high handout validation score of 84.50. The results of this study contributed significantly to students' understanding of bird diversity in mangrove ecosystems, so that it can be integrated as supporting material in the Biodiversity of Living Things course. It is expected that handouts based on local potential can be effective in improving students' understanding of bird diversity in mangrove ecosystems, and contribute to efforts to conserve and manage mangrove ecosystems in the region.